2021
DOI: 10.3390/ijms22063118
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of 1-Naphthylphthalamic Acid in Conspicuous Local Stem Swelling of Succulent Plant, Bryophyllum calycinum: Relevance to the Aspects of Its Histological Observation and Comprehensive Analyses of Plant Hormones

Abstract: The mode of action of 1-naphthylphthalamic acid (NPA) to induce conspicuous local stem swelling in the area of its application to the growing internode in intact Bryophyllum calycinum was studied based on the aspects of histological observation and comprehensive analyses of plant hormones. Histological analyses revealed that NPA induced an increase in cell size and numerous cell divisions in the cortex and pith, respectively, compared to untreated stem. In the area of NPA application, vascular tissues had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…paste, where lanolin alone did not affect morphological changes in the internode segments. This situation was demonstrated in previous works [27,31,35]. In the stem of B. calycinum, IAA applied to a decapitated shoot or internode explants prevented the formation of the SAZ induced by JA-Me [31,33].…”
Section: Effect Of Ja-me On Gibberellinssupporting
confidence: 74%
See 1 more Smart Citation
“…paste, where lanolin alone did not affect morphological changes in the internode segments. This situation was demonstrated in previous works [27,31,35]. In the stem of B. calycinum, IAA applied to a decapitated shoot or internode explants prevented the formation of the SAZ induced by JA-Me [31,33].…”
Section: Effect Of Ja-me On Gibberellinssupporting
confidence: 74%
“…Analyses of plant hormones were performed according to the methods reported previously [27,35,[54][55][56]. At 6 to 7 days after treatment with JA-Me, the below (nonsenescent, green) and above (senescent, yellow) parts of ca.…”
Section: Analyses Of Plant Hormones In Relation To the Formation Of The Secondary Abscission Zone Induced By Methyl Jasmonatementioning
confidence: 99%
“…The accumulated endogenous auxin in inflorescence stems has been considered to be important for the hypergravity-enhanced expression of genes related to lignin biosynthesis. Marasek-Ciolakowska et al (2021) showed that the application of 1-naphtylphtalamic acid, an inhibitor of polar auxin transport, induced conspicuous local stem swelling in the area of its application and significantly increased endogenous IAA level in the area of stem swelling in Bryophyllum calycinum. In etiolated pea seedlings hypergravity conditions substantially enhanced stem swelling and reduced elongation growth of the epicotyls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of endogenous hormones, including IAA, ABA, GA, and zeatin (ZT) in leaves and roots were determined according to the methods previously reported by Marasek-Ciolakowska et al (2021) . Frozen leaves or roots (2.5 g) were ground with a mortar and pestle to a powder in liquid nitrogen, then the powder was rapidly transferred to a 50 mL centrifuge tube and extracted with 20 mL of 80% methanol at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%